2021
DOI: 10.4103/ijo.ijo_3037_20
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic manifestations in the COVID-19 clinical spectrum

Abstract: Purpose: The aim of this study was to determine the frequency and various types of ophthalmic manifestation of patients with COVID-19. Methods: This is a prospective observational study conducted on patients with SARS-Co-V-2 infection, at a dedicated tertiary COVID-19 hospital in South India from April 1 to July 31, 2020. At the time of their admission to the COVID hospital, demographic data such as name, age, sex was recorded. A thorough history regarding the onset, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…According to several studies, ocular symptoms are uncommon and unlikely to represent the presenting clinical impression in COVID-19 infection. 19 Furthermore, no epiphora, no secretion, or decreased vision has been reported. 20 Other studies concluded no eye problem reports in Thailand that could be related to the severity of the disease and low sample size.…”
Section: Adults’ Ocular Manifestationsmentioning
confidence: 99%
“…According to several studies, ocular symptoms are uncommon and unlikely to represent the presenting clinical impression in COVID-19 infection. 19 Furthermore, no epiphora, no secretion, or decreased vision has been reported. 20 Other studies concluded no eye problem reports in Thailand that could be related to the severity of the disease and low sample size.…”
Section: Adults’ Ocular Manifestationsmentioning
confidence: 99%
“…The reported prevalence of ocular manifestations of COVID-19 infection from various studies is 2-32%, in our study the ocular manifestations and morbidity due to COVID-19 infected subjects was 15.8%, this finding from our study was comparable with existing literature. [17][18][19][20][21][22] In the current study, a relatively rare condition like pseudotumor cerebri was seen in three of the study participants. This was comparable to the findings from a study done by Noro F, et al who explained and reported pseudotumor cerebri post COVID-19 infection as a persistent cause of headache.…”
Section: Discussionmentioning
confidence: 96%
“…The most common and easily identifiable ocular manifestations of the SARS-CoV-2 have been reported in the ocular surface (e.g. conjunctival hyperemia, chemosis, and epiphora) [ 4 10 ].…”
Section: Introductionmentioning
confidence: 99%